(untitled) (Research, Society and Development, 2020)
Biodiesel has great potential to replace petroleum diesel. Although its production from microalgae generates several environmental advantages (consumption of atmospheric carbon dioxide and effluents can be used as a source of nutrients), it presents difficulties to be implemented in the energy matrix of several countries due to its high cost associated with many stages of the production process. Thus, the present work has as main aim to analyze the influence of the temperature and time variables in the production of biodiesel via direct transesterification of microalgae biomass of the species Nannochloropsis oculata, identifying the conditions that provide maximum yield of the extract rich in biodiesel. Through the experimental method, it was possible to grow microalgae of the species Nannochloropsis oculata and, from the biomass obtained, produce biodiesel through the direct transesterification reaction. The formation of biodiesel was verified by means of FTIR analysis that showed the presence of esters in the final product, with the maximum yield points being obtained in the conditions 70 ºC and 60 min and at 110 ºC and 60 min.